The Partisan Gap : Why Democratic Women Get Elected But Republican Women Don't - Elder, Laurel (Book collections on Project MUSE., 2021)
"This book explores the reasons behind the contrasting dynamics of women's representation in elective office and offers an explanation for why Democratic women have made consistent and impressive gains while Republican women's representation in elective office has stalled and in many cases reversed"--